Pelatihan Pembuatan Cairan Disinfektan Sebagai Upaya Pencegahan COVID-19 Di Jemaat Horeb Kuanheum - Hartini Solle; Merpiseldin Nitsae; Sonya Titin Marlina Nge; Arnold Ch. Hendrik; Mellissa E.S Ledo; Henderina Mowata; Joenrith Agrid (J.Abdimas: Community Health, 2022)
A group of viruses that can cause disease in humans are coronavirus disease (Covid-19). Several types of COVID-19 are capable of causing infections in the human respiratory tract through coughing and colds such as SARS and MERS. The spread of Covid-19 has become so widespread that the WHO has declared it a world pandemic. The increase in the number of sufferers can be caused by a lack of public awareness of healthy living behavior. This training is carried out so that the people of the Kuanheum village can know and be able to prevent the spread of Covid-19. This activity uses community education methods in the form of socialization and training to the community. The activity was carried out actively and enthusiastically, attended by 29 community representatives, especially young people, housewives and village officials. Training on making disinfectant liquid using household materials that are easy to obtain and inexpensive. Activities are carried out in 4 stages: 1) site survey; 2) the implementation was carried out at GMIT Horeb, Kuaheum; 3) evaluation by the PkM team. Based on the evaluation carried out, it can be seen that of the 29 respondents who gave feedback on activities for understanding the manufacture of disinfectant liquid before being given training materials (P1) were in the sufficient (28.6%) and very good (61.9%). This activity has a positive impact on the understanding and skills of the Horeb Kuanheum congregation about preventing the spread of Covid-19. Keywords: Disinfectant, Practice, Respondent, Socialization, Virus.